2020
DOI: 10.1002/advs.202001398
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐Based Olefin/Paraffin Separations

Abstract: Efficient olefin/paraffin separation is a grand challenge because of their similar molecular sizes and physical properties, and is also a priority in the modern chemical industry. Membrane separation technology has been demonstrated as a promising technology owing to its low energy consumption, mild operation conditions, tunability of membrane materials, as well as the integration of physical and chemical mechanisms. In this work, inspired by the physical mechanism of mass transport in channel proteins and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 193 publications
(251 reference statements)
0
94
0
Order By: Relevance
“…Peaks I( 156 meV), III (137 meV) and V(114 meV) can be assigned to the symmetric, asymmetric and out-of-plane bending modes of the framework -CH groups,consistent with Membrane-based separation techniques are widely considered to be energy-efficient alternatives to traditional distillation processes. [31][32][33] MMMs can effectively improve the trade-off between selectivity and permeability in pure polymer-based membranes by incorporating porous fillers. [33] Although polymer-based thin-films and MMMs have been studied intensively for the separation of various gas mixtures, such as H 2 /CO 2 , [34][35][36] CO 2 /N 2 , [37] CO 2 /CH 4 [38][39][40] and O 2 /N 2 , [41] polymer-based membranes have shown limited separation factors or permeability [42][43][44] for the separation of C 3 H 6 /C 3 H 8 , and such studies based upon MOF-incorporated MMMs have only been reported in limited cases,such as ZIF-8, ZIF-67 and SIFSIX [32,[45][46][47][48] (Figure 4, Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…Peaks I( 156 meV), III (137 meV) and V(114 meV) can be assigned to the symmetric, asymmetric and out-of-plane bending modes of the framework -CH groups,consistent with Membrane-based separation techniques are widely considered to be energy-efficient alternatives to traditional distillation processes. [31][32][33] MMMs can effectively improve the trade-off between selectivity and permeability in pure polymer-based membranes by incorporating porous fillers. [33] Although polymer-based thin-films and MMMs have been studied intensively for the separation of various gas mixtures, such as H 2 /CO 2 , [34][35][36] CO 2 /N 2 , [37] CO 2 /CH 4 [38][39][40] and O 2 /N 2 , [41] polymer-based membranes have shown limited separation factors or permeability [42][43][44] for the separation of C 3 H 6 /C 3 H 8 , and such studies based upon MOF-incorporated MMMs have only been reported in limited cases,such as ZIF-8, ZIF-67 and SIFSIX [32,[45][46][47][48] (Figure 4, Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…Membrane‐based separation techniques are widely considered to be energy‐efficient alternatives to traditional distillation processes [31–33] . MMMs can effectively improve the trade‐off between selectivity and permeability in pure polymer‐based membranes by incorporating porous fillers [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Peaks I(156 meV), III (137 meV) and V( 114 meV) are assigned to the symmetric,a symmetric and Membrane-based separation techniques are widely considered to be energy-efficient alternatives to traditional distillation processes. [31][32][33] MMMs can effectively improve the trade-off between selectivity and permeability in pure polymer-based membranes by incorporating porous fillers. [33] Although polymer-based thin-films and MMMs have been studied intensively for the separation of various gas mixtures, such as H 2 /CO 2 , [34][35][36] CO 2 /N 2 , [37] CO 2 /CH 4 [38][39][40] and O 2 /N 2 , [41] polymer-based membranes have shown limited separation factors or permeability [42][43][44] for the separation of C 3 H 6 /C 3 H 8 , and such studies based upon MOF-incorporated MMMs have only been reported in limited cases,such as ZIF-8, ZIF-67 and SIFSIX [32,[45][46][47][48] (Figure 4, Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, inorganic membranes' fabrication costs are high in comparison to other two membranes. [28][29][30][31] To increase consistency and permeability of mixed matrix, application of zeolite-based materials has attracted much attention of the scientists in recent years. [32][33][34] Owing to high thermal and chemical stability, ZIFs have attracted more attention than that of metal-organic framework.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inorganic membranes’ fabrication costs are high in comparison to other two membranes. [ 28–31 ]…”
Section: Introductionmentioning
confidence: 99%